Constraints Affecting the Increase of Sago Production: A Case of Melanau Rural Youth’s Participation in Sago Industry in Sarawak, Malaysia - Siti Zanariah, Ahmad Ishak; Ahmad Nizar, Yaakub; Awang Ideris, Awang Daud; Siti Haslina, Hussin; Adibah, Yusuf (Human Resource Management Academic Research Society (www.hrmars.com), 2021)
Sago industry which comprises sago cultivation, processing and sago-based food entrepreneurship has its own youth participation challenges. Consequently, the study aimed at determining constraints factors affecting rural youth sago producers. The constraint factors, namely internal and external factors are developed from modelling reason action theory. Data were collected from 200 youth sago producers in Mukah Division via face-to-face interview using a close-ended questionnaire. The data were analysed by means of descriptive statistics, exploratory factor analysis and binary logistic regression model. The descriptive statistic showed the pattern of youth participation in the sago industry. The result of exploratory factor analysis identified six constraints factors affecting youth sago producers; commodity price, new knowledge, physical infrastructure, income, assistance and training. The result of binary logistic regression showed that the low participation of part-time to full-time participation of youth sago producers is significantly influenced by new knowledge, physical infrastructure and training constraint factors. The study suggests rural youth requires technological advancement in the sago industry. In addition, the findings may provide useful information to the relevant stakeholders to re-evaluate the assistance and support programs to increase the participation and productivity of the Melanau youth. Furthermore, encouragement be given to more non-Melanaus to participate in sago industry.